Emergency vaccine immunization protects hamsters against acute leptospirosis. (December 2021) - Zhang, Shilei; Wu, Dianjun; Tang, Ruibo; Zhang, Wenlong; Cao, Yongguo
Abstract: Leptospirosis, caused by pathogenic Leptospira, is a global critical zoonotic disease in terms of mortality and morbidity. Vaccines are often used to prevent leptospirosis. However, few studies have reported the therapeutic effect of a vaccine against Leptospira infection. This study demonstrates the efficacy of the emergency vaccine immunization against acute leptospirosis in hamsters. Treatment with a whole-cell vaccine ( Leptospira interrogans serovar Lai) at 24 h post-infection improved the survival rate of hamsters with lower leptospiral burden and minor pathological damage to organs. The vaccine also protected against multiple Leptospira serotypes acute infection. However, the protective effect of the vaccines was lost when beginning treatment at 36 h or 48 h post-infection. These results indicated that vaccines could treat acute leptospirosis in hamsters, but only if immunization is within 24 h after infection. Highlights: Treatment with vaccines against acute homologous Leptospiral (56601) acute infection. Treatment with vaccines elevates gene expression of TLR2, TLR4 and inflammatory factors during leptospira infection. Treatment with vaccines reduces the leptospiral burden of organs and relieves pathological damage. Treatment with vaccines against heterologous leptospiral acute infection. Abstract : Author Summary: Leptospirosis is one of the most important neglected emerging zoonotic diseases; it usually spreads in bursts due to natural disasters or large-scale water pollution. Vaccines are often used to protect against leptospirosis; it has not been reported whether leptospiral vaccines can play a therapeutic role in post-infection. This study demonstrated that treatment with a whole dead vaccine within 24 h post-infection improved the survival rate of hamsters with lower leptospiral burden and minor pathological damage in their organs. These results indicated that vaccines may be useful for prevention but also therapeutic action against leptospirosis.